'Each phrase go be soaked in salt' – vernacular worlds in Derek Walcott's poetry. Issue 5 (3rd May 2020) - Neumann, Birgit
ABSTRACT: The essay examines the use of the vernacular in some of Derek Walcott's poems, arguing that the vernacular performs a paradoxical task: While it indexes transcultural entanglement and plurality, it also remains attuned to local specificities and linguistic difference. The vernacular, in poems such as 'Names' (1976), 'Sainte Lucie' (1976), 'The Schooner Flight ' (1979), and Omeros (1990), is a carefully stylised, genuinely transcultural idiom that straddles different cultures, periods, and spaces and that stubbornly blurs the distinction between orality and literariness. At the same time, the vernacular symbolises Caribbean experiences of exchange and thickens the linguistic plurality at the heart of this region to evoke histories of colonisation and translocation. Focussing on the poetic dimension of the vernacular, the essay illustrates how this idiom comes to function as a transformative component of the poems' world-making. Detached from any fixed and monolithic territory, the vernacular encourages translations between non-synchronous entities and invites readers to understand the world in terms of its immanent relationality.